Catalytic activity of iron phthalocyanine for the oxidation of thiocyanate and L-cysteine anchored on Au(111) clusters. Issue 17 (22nd November 2019) - Castro-Latorre, Pablo; Miranda-Rojas, Sebastián; Barrientos, Lorena; Mendizabal, Fernando
ABSTRACT: We studied the oxidation reactions of thiocyanate and L-cysteine on iron phthalocyanine (FePc) coupled via a bridging ligand of the 4-mercatopyridine (4MP) type to a gold cluster (Au26 ), aiming to simulate a modified gold electrode. Theoretical models have been used based on the framework of density functional theory. Several mechanistic pathways are explored for the study of these reactions, finding that the most favorable mechanism involves an electron transfer process as the rate-determining step. Along the process, the ability of the gold cluster to act as an electron acceptor facilitating the reactions was detected. In addition, the proposed models presented a correlation between the energy obtained for the rate-determining step of the reaction and the experimental oxidation potentials of the thiocyanate and L-cysteine.